The Relationship Between Interest in Reading and Motivation to the Results of Learning Arabic in Islamic Junior High State School - Banjari, Zainuddin; Agby, Zenny; Khan, Eguy (Journal International of Lingua and Technology, 2022)
Low interest in reading and student learning motivation due to lack of support from the family, community, and school to increase interest in reading and learning motivation of students. This study has the aim of knowing the relationship between interest in reading and learning motivation to Arabic learning outcomes in Islamic Junior High State School. Researchers use quantitative research types. The data collected is interest in reading and student learning motivation using the questionnaire and interview methods. The data were analyzed with students filling out the questionnaire provided, and researchers conducted a structured interview with the teacher who taught Arabic in the Islamic Junior High State School. The results of this study can find out the relationship between interest in reading and learning motivation to Arabic learning outcomes. If the interest in reading and student learning motivation is low, learning outcomes are also low, but if interest in reading and motivation is high, learning outcomes will certainly also be high. The interest in reading and learning motivation is very important to be improved in the learning process in order to maintain good learning outcomes and develop student learning outcomes.